EBCOG position statement: Gender neutral HPV vaccination for young adults. (March 2020) - Verheijen, Rene H.M.; Mahmood, Tahir; Donders, Gilbert; Redman, Charles W.E.; Wood, Paul
Abstract: Human Papilloma Virus (HPV) has been implicated in the initiation of several types of cancers in both females and males. Therefore, it is imperative that national immunization programs should ensure that both young women and young men receive full immunization for herd immunity in their teenage years. A recent review confirmed that vaccination of boys and girls would be most cost-effective under the circumstances that both individual costs and coverage are low. By doing so, it would be possible to reduce the incidence of HPV-related malignancies to a large extent at later age in both sexes.